Broadening the healthy aging paradigm: inclusion of gestation, development, and reproductive health - Yao, Lan; Eikelboom, John; Macnab, Andrew; Yu, Zhuo; Cao, Yanhong; Wei, Wei; Sun, Shuqiu; Khalil, Asma; Cho, William C.; Qamar, Farah Naz; Kremsner, Peter; Oliu-Barton, Miquel; et al. (Advanced biology, 2025)
The prevailing focus of lifespan health research has predominantly centered on “healthy aging”. This oversight may hinder the understanding of health across the lifespan, as disorders in earlier stages can substantially impact overall health and longevity. Aging, conceptually, begins at gestation. The trajectory of an individual's health is influenced from the earliest stages of life, where adverse conditions can set a foundation for lifelong health challenges. For example, suboptimal conditions during gestation leading to premature birth can predispose individuals to various health issues later in life. Additionally, precocious puberty defined as the onset of sexual maturity before eight years of age or early menopause - occurring before 50 years of age requires medical intervention and is indicative of atypical aging processes. To address these critical gaps in lifespan health research, the expansion of medical lexicons and research categorizations is advocated to include “healthy gestation,” “healthy development,” and “healthy reproduction” alongside “healthy aging.” This broader terminology will enable a more comprehensive investigation of disorders at all life stages. An integrative approach underscores the interconnectedness of all life stages and the continuous nature of aging, advocating for a seamless continuum in health research and interventions from gestation through late adulthood.